2018
DOI: 10.1111/jth.14251
|View full text |Cite
|
Sign up to set email alerts
|

Delimiting the autoinhibitory module of von Willebrand factor

Abstract: Background The hierarchical hemostasis response involves a self-inhibitory feature of von Willebrand factor (VWF) that has not been fully characterized. The residues flanking the A1 domain of VWF are important in this self-inhibition by forming an autoinhibitory module (AIM) that masks the A1 domain. Objectives To delimit the AIM sequence and to evaluate the cooperative interplay between the discontinuous AIM regions. Methods ELISA, flow cytometry, a thermal stability assay and hydrogen-deuterium exchange (HDX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(56 citation statements)
references
References 35 publications
3
49
4
Order By: Relevance
“…For example, the A1 domain elongates in shear flow into a conformation with high affinity for GPIbα ( 18 ). An autoinhibitory module has been identified that flanks and binds the A1 domain, deletion of which activates the A1 domain ( 63 , 64 ), suggesting that shear flow produces dissociation of the autoinhibitory module. Additionally, shear flow has been reported to promote unfolding of the VWF A2 domain and drive self-association of VWF ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the A1 domain elongates in shear flow into a conformation with high affinity for GPIbα ( 18 ). An autoinhibitory module has been identified that flanks and binds the A1 domain, deletion of which activates the A1 domain ( 63 , 64 ), suggesting that shear flow produces dissociation of the autoinhibitory module. Additionally, shear flow has been reported to promote unfolding of the VWF A2 domain and drive self-association of VWF ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cleaved VWF also supported slower platelet rolling than intact VWF, indicating that cleaved VWF adopts a conformation that supports a longer or stronger interaction with platelets. The A1 domain of VWF forms an autoinhibitory module that masks the A1 domain . Cleavage of VWF just prior to the A1 domain may release it from protection by the D3 domain and/or destabilize the N‐terminus of the A1 domain to expose the GPIbα binding site .…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen deuterium exchange mass spectrometry (HDX‐MS) was performed largely as described on a Waters HDX system with nanoAcquity UPLC (Waters, Milford, MA, USA) and Micromass Q‐ToF Premier mass spectrometer. Samples were measured in tandem using the same buffers to minimize the difference in back exchange.…”
Section: Methodsmentioning
confidence: 99%